A new species of jumping pitviper of the genus Atropoides (Serpentes: Viperidae: Crotalinae) from the Sierra de Botaderos and the Sierra La Muralla, Honduras - Smith, Eric N.; Ferrari-Castro, Jorge A. (Zootaxa, 2008)
We describe a new species of pitviper of the genus Atropoides from the Sierra de Botaderos and La Muralla, Honduras. The new species is easily distinguished from all other members of the genus, except A. picadoi from Costa Rica and Panama, by possessing more ventral scales (140 vs. 103–138). This new species differs from A. picadoi in being relatively small, less than 600 mm in total length (vs. reaching > 750 mm), having the posterior third of the body venter heavily melanized (vs. more than 50%), less than 50% of the underside of the tail melanized, and the postorbital stripe covering more than 50% of only one or two scales from the first temporal row and covering completely only the last scale of the row, at most (vs. 3–4 more than 50% melanized and the last two scales in the row usually completely melanized). In addition to morphological characters, molecular evidence also differentiates this new species from the other species of Atropoides (as recognized by Castoe et al. 2005). Using mitochondrial gene sequence data, they found the new species described herein to represent the sister species of A. occiduus, with 5.7 % sequence divergence separating these two taxa.